How skills and parental valuation of education influence human capital acquisition and early labor market return to human capital in Canada - Steven F. Lehrer (Queen's University, Department of Economics, 2019)
Using the Youth in Transition Survey we estimate a Roy model with a three dimensional latent factor structure to consider how parental valuation of education, cognitive skills and non-cognitive skills influence endogenous schooling decisions and subsequent labour market outcomes in Canada. We find the effect of cognitive skills on adult incomes arises by increasing the likelihood of obtaining further education. Further, we find that both non-cognitive skills and parental valuation for education play a larger role in determining income at age 25 than cognitive skills. Last, our analysis uncovers striking differences between men and women in several of the estimated relationships. Specifically, simulations of the estimated model illustrate that i) among the low skilled, women have much higher college graduation rates, ii) the age 25 earnings gradient by either skill measure is much flatter for women, and iii) parental valuation of education plays a larger role in influencing young women than men.
Keywords: J24; I26; C38; 330; skills; schooling decisions; early labour market outcomes; gender differences; parental valuation of education